2014
DOI: 10.15829/1560-4071-2014-12-31-37
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hemodynamic Interrelations of Arrhythmia Course in Children of 0 to 7 Years Old

Abstract: Цель. Оценить клинические и гемодинамические параллели у детей дошколь-ного возраста с аритмиями в различных возрастных группах. Материал и методы. Обследовано 195 детей с идиопатическими аритмиями в возрасте от 0 до 7 лет -82 пациента с синдромом WPW, 55 детей с пред-сердными тахикардиями, 7 детей с АВУРТ, 13 -с желудочковыми тахикарди-ями (ЖТ), 38 детей с желудочковыми и наджелудочковыми экстрасистолиями (изолированной, групповой и их сочетанием). Возрастные группы: 1 -дети до 1 года (n=72; 37%); 2 -дети от … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Sustained tachycardia occurred in patients with atrial ectopic tachycardia ( n = 47.3%). Incessant atrial ectopic tachycardia was observed in eight patients (5%) at the age of 1 year old 4 …”
Section: Study Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustained tachycardia occurred in patients with atrial ectopic tachycardia ( n = 47.3%). Incessant atrial ectopic tachycardia was observed in eight patients (5%) at the age of 1 year old 4 …”
Section: Study Methodsmentioning
confidence: 99%
“…Incessant atrial ectopic tachycardia was observed in eight patients (5%) at the age of 1 year old. 4 …”
Section: Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…кардіоміопатії, а при моделюванні тахііндукованої кардіоміопатії у тварин в експерименті одержано згладжені реакції на β-адренергічну стимуляцію, що автори пов'язують зі зменшенням щільності β-адренергічних рецепторів [6,7]. Розвиток вАКМП із ремоделюванням порожнин і формуванням порушень систолічної та діастолічної функцій є прогностично несприятливим фактором перебігу будь-якого варіанта аритмій у дітей і підлітків та потребує призначення не тільки засобів корекції порушень ритму, але й засобів запобігання розвитку симптомів вАКМП і подальшого прогресування систолічної та діастолічної дисфункції серця [8][9][10][11]. З цією метою використовуються засоби патогенетичної та метаболічної дії.…”
unclassified